Pengaruh Belanja Pemerintah Bidang Pendidikan, Kesehatan dan PDRB terhadap IPM di Provinsi Jawa Tengah (Studi Kasus 35 Kab/kota Provinsi Jawa Tengah) - Sindhu Ayu Triadita Prastiwi; Herniwati Retno Handayani (Universitas Diponegoro, 2021)
The current focus of development is more on human development. Through improving the quality of human resources, it can improve social welfare and state development. For this reason, the government is trying to improve the quality of human development through budget allocations in the health and education sectors which continue to increase every year. The purpose of this study was to analyze the effect of government spending on education, health, and gross regional domestic products (GRDP) on the human development index in 35 districts/cities of Central Java province in 2014-2019. The type of data used is secondary data in 35 districts/cities in Central Java from 2014-2019. The analysis method used in this research is panel data regression using Fixed Effect Model (FEM) with Generalized Least Square (GLS) weighting. The results in this study are the health spending and GRDP variables have no significant effect on HDI, while the education spending variable has a significant effect on HDI.